Cinderella - Rossini, Gioacchino 1792-1868.; Montresor, Beni. (New York Alfred A. Knoft, 1965)
Recounts Rossini's operatic version of the tale of the mistreated cinder maid who stepped into a glass slipper and the arms of her Prince Charming.
The narration (without the music)
Keywords: Operas -- Stories, plots, etc; Fairy tales